5, 5′-Diamino-BIPHEP ligands bearing small selector units for non-covalent binding of chiral analytes in solution. Issue 86 (11th September 2015) - Storch, G.; Siebert, M.; Rominger, F.; Trapp, O.
Abstract : A dynamic axially chiral BIPHEP-ligand with 3, 5-dichlorobenzoyl amide selector units for non-covalent binding of phenylalanine derivatives has been developed. Abstract : A dynamic axially chiral BIPHEP-ligand with 3, 5-dichlorobenzoyl amide selector units for non-covalent binding of phenylalanine derivatives has been developed. Interaction studies in solution were performed with rhodium(i ) complexes under exclusion of the metal being involved in binding. ( R ax, S Phe ) and ( S ax, S Phe ) adducts were observed as significantly separated species in NMR spectroscopy.